2020
DOI: 10.1093/jscr/rjaa256
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple advanced synchronous colorectal cancers successfully treated by laparoscopic surgery: a case report

Abstract: Among synchronous colorectal cancers (SCRCs) reported previously, the incidence of quadruple advanced SCRCs is very rare. We present the case who underwent laparoscopic two-segment resection of the colon requiring two anastomoses that was performed for quadruple advanced cancers, and four tumors were curatively removed. There were no signs of recurrence at 64 months after surgery. Laparoscopic surgery provided less invasiveness even for quadruple advanced SCRCs in terms of early recovery with an acceptable lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(11 reference statements)
1
1
0
Order By: Relevance
“…Meanwhile, adenocarcinomas are more commonly seen in SCRC patients. As reported in other cases with triple [ 7 , 8 ] or quadruple [ 9 ] SCRC, the adenocarcinomas were frequently identified in the sigmoid colon, ascending and descending colon respectively. The presence of various histology types in the same patient indicated that carcinogenesis underlying multiple tumor lesions of SCRC might be different.…”
Section: Discussionsupporting
confidence: 76%
“…Meanwhile, adenocarcinomas are more commonly seen in SCRC patients. As reported in other cases with triple [ 7 , 8 ] or quadruple [ 9 ] SCRC, the adenocarcinomas were frequently identified in the sigmoid colon, ascending and descending colon respectively. The presence of various histology types in the same patient indicated that carcinogenesis underlying multiple tumor lesions of SCRC might be different.…”
Section: Discussionsupporting
confidence: 76%
“…Synchronous colorectal cancers (SCRCs) are characterized by the simultaneous occurrence of multiple primary tumours in the same patient [1]. Synchronous malignancies most commonly occur in the colon among other organs [2][3][4].…”
Section: Laparoscopic Subtotal Colectomy With Complete Mesocolic Exci...mentioning
confidence: 99%